Debating Moderate Islam - Muqtedar Khan (International Institute of Islamic Thought, 2005)
Since the September 11, 2001, attacks on the United States, there have been several conversations about the different interpretations of Islam, its impact on Muslim politics, and the relationship between Islam and the West. This debate gained renewed vigor after the London attacks on July 7 and 21, 2005. Scholars and policymakers agree that a politically angry and intellectually narrow interpretation of Islam – loosely referred to as militant or radical Islam – is exacerbating the already rampant anti-Americanism in the Muslim world and encouraging terrorist responses to real and perceived injustices. Some analysts assert that the United States is completely innocent and thus blame radical Islamists alone for all of the problems in the world, while others totally ignore the existence of extremism in the Muslim world and blame the United States for all of the ills of our times. Most people are somewhere in between. Regardless of where one stands in this debate, there is now a growing consensus that those on the moderate side in the Muslim world must assert themselves and join the battle against extremism. Western governments are being advised to actively welcome the help and cooperation of moderate Muslims in order to ensure that the war against extremism does not become – or appear to be – a war against Islam. This policy idea of including moderate Muslims as allies against extremism in the Muslim world has generated an interesting debate about what moderation really means and who is a moderate Muslim. In this special issue of the American Journal of Islamic Social Sciences, prominent voices from the policy community, the academic community, and the American Muslim community come together to debate who is a moderate Muslim and just what moderation means in a theological as ...